A discrete choice experiment on consumer's willingness-to-pay for vehicle automation in the Greater Toronto Area. (July 2021) - Wang, Kaili; Salehin, Mohammad Faizus; Nurul Habib, Khandker
Abstract: Autonomous vehicles (AVs) are around the corner, and adopting this technology will create a revolution in our transportation system. Mass adoption of AVs might have both positive and negative impacts to travel demand and the transportation system. How we adopt, matters. Several studies show that private AVs might lead to more travel demand and dispersed urban patterns, but shared AVs might contribute otherwise. This paper presents an overview of and a modelling work on a dataset collected in the Greater Toronto Area (GTA) to understand consumers' willingness-to-pay for various automation levels in their vehicles simultaneously with private and shared ownership types. The study used 190 records from a reasonably representative sample collected from the study area. Heteroskedastic error-component mixed multinomial and nested logit models are formatted for different vehicle ownerships in this study. Strong inertia effect of staying with private conventional vehicles (PCVs) is identified. We also discover that private vehicle buyers will find level 4 vehicles attractive, whereas car-sharing service users will favour level 5 vehicles. For level 4 vehicles, consumers are willing to pay from CAN 10, 800 to CAN 29, 800, depending on the vehicle price. We also find that respondents' age, family members' health conditions, commuting conditionals, and household incomes will influence their willingness to pay for owning AVs.